Adaptação transcultural do hospital Ethical Climate Survey para enfermeiros brasileiros - Lanes, Taís Carpes (2020)
The ethical climate can be defined as the perception of health professionals regarding the ethical treatment of care issues and relationships in their work environment. This theme has been evaluated, through some instruments, in hospital services. Among the instruments, the Hospital Ethical Climate Survey is one of the most used to assess the ethical climate among hospital nurses. Therefore, the general objective of adapting the Hospital Ethical Climate Survey instrument to Brazilian culture was to cross-culturally. It has the specific objectives: to characterize the population in terms of sociodemographic and work data, and to assess the perception of hospital nurses about the ethical climate. This is a methodological study, which followed seven steps for the operationalization of the adaptation: Direct translation; Synthesis of translations; Back-translation; Multidisciplinary committee; Expert panel; Pilot test and instrument validation. The population of this study consisted of nurses from the University Hospital of Santa Maria, who completed the instruments of sociodemographic and labor characterization and the Hospital Ethical Climate Survey - Brazilian version, from April to July 2019. The data analysis was performed by psychometric tests and descriptive statistics. The project is linked to the matrix, which was approved by the Research Ethics Committee of the Federal University of Santa Maria, under the Presentation Certificate number for Ethical Appreciation: 92702318.9.0000.5346 and opinion 049598. Regarding the results, initially in the adaptation stage, some linguistic adjustments were necessary to maintain the original meaning of the instrument. Then, in the validation stage, 269 nurses participated in the study, 88,1% were female and with an average age of 40,6 years (Standard Deviation = 8,65). In the performance of the psychometric tests, the Kappa weighted quadratic value and intraclass correlation coefficient, ranging from 0,15 to 0,74, were obtained, being suitable for the sample of this study. All factorial loads were greater than 0,4, ranging from 0,445 to 0,859. With regard to reliability, the Cronbach's alpha value was 0,93, and the confirmatory analysis demonstrated the adequacy of the model with five factors and 26 validated items. Correlations by factors and the total were considered moderate to strong. The cut-off point of 3,5 for the ethical climate was tested and confirmed by the K-Nearest Neighbor method. As for the assessment of the ethical climate, nurses' positive perception of the ethical climate was evident (3,68 ± 0,55). Among the five assessment factors, “physicians” had the lowest score (3,26 ± 0,70), while the “peers” factor had a higher score (4,07 ± 0,57). It is concluded that the version of the instrument adapted to Brazilian Portuguese was considered valid and reliable in this sample. In addition, the ethical climate in general was perceived as positive with small variations between the five factors of the instrument, which can be enhanced through strategies that encourage interpersonal relationships between the multidisciplinary team, management and patients. It is suggested that the Hospital Ethical Climate Survey - Brazilian version be applied to other hospital services, from different contexts, making associations with aspects related to work organization, worker health and patient safety.